PENGARUH TARIF PAJAK, MEKANISME PEMBAYARAN PAJAK, KESADARAN WAJIB PAJAK, DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI SURABAYA BARAT - Putri, Mayka; Mardiana, Lilik (Pascasarjana Universitas Sultan Ageng Tirtayas, 2024)
This study aims to analyze the effect of tax rates, tax payment mechanisms, taxpayer awareness, and tax sanctions on MSME taxpayer compliance. The object of this research is MSME taxpayers in West Surabaya. The sampling technique in this study used purposive sampling. Data collection was carried out through a questionnaire and the sample obtained was 74 respondents. Each question is measured using a Likert scale. The data analysis technique in this study used the help of the IBM SPSS Statistic 23 application. The results of this study indicate that hypothesis (1) can be accepted which shows that tax rates have a positive and significant effect on MSME taxpayer compliance. Hypothesis (2) is accepted which shows that the tax payment mechanism has a positive and significant effect on MSME taxpayer compliance. Hypothesis (3) is rejected, which shows that taxpayer awareness has no significant effect on MSME taxpayer compliance. Hypothesis (4) is rejected which shows that tax sanctions have no significant effect on MSME taxpayer compliance.